The changing dynamics of the Western Balkans on the road to European Union membership: An update - Marek Dabrowski; Luca Léry Moffat (Bruegel, 2024)
The slow pace of European Union enlargement to the Western Balkans can be attributed to EU member countries losing their political appetite for further enlargement in the 2010s and early 2020s, and to the fact that Western Balkan countries have failed to make visible progress in meeting the criteria for EU accession The income per capita convergence of Western Balkan countries towards the German level (as a proxy for the EU) has been rather slow, with some acceleration in the second half of the 2010s and early 2020s. However, Western Balkan countries continue to suffer from several socio-economic vulnerabilities, including high unemployment rates (especially of young people) and low rates of participation of women in the workforce. After the beginning of the war in Ukraine in 2022, the EU gave higher political priority to further enlargement. It opened a new eastern front of potential enlargement (Ukraine, Moldova and Georgia) and activated the stalled accession process in the Western Balkans. Bosnia and Herzegovina obtained candidate status in December 2022 and was approved for accession negotiations in March 2024. Accession negotiations with Albania and North Macedonia were started in July 2022. With the new government in Montenegro from the end of 2023, the accession negotiation with this most advanced candidate country moved forward. Overcoming the legacy of the tragic conflicts in the 1990s is another key geopolitical challenge in the region. This involves the normalisation of Serbia-Kosovo relations and the reconciliation process inside Bosnia and Herzegovina. In the economic sphere, speeding up income per capita convergence with the EU requires further domestic economic reforms, accelerating intra-regional economic integration and creating new EU initiatives to support growth and social cohesion in the Western Balkans. Accelerating EU accession negotiations with indicative target dates, at least for frontrunners, can reduce the perception of geopolitical and economic uncertainty and stimulate foreign direct investment inflows.
Keywords: 330; European neighbourhood policy; eu governance; eu budget; global governance